A MATLAB‐based educational platform for analysis of slope stability. Issue 2 (22nd November 2021) - Yin, Zhen‐Yu; Teng, Jing‐Cheng; Wang, Han‐Lin; Jin, Yin‐Fu
Abstract: This study presents a computer‐aided educational platform, namely, ErosSSA (Eros‐Slope‐stability‐analysis) developed by the geotechnical group in the Hong Kong Polytechnic University, to provide civil engineering students and young industrial engineers a better understanding of the analysis of slope stability. The platform is developed under the MATLAB environment, with a clear framework and a graphical interface. Using this platform, the rotational landslides can be generally analyzed, considering a circular slip surface and the factors of safety defined with respect to basic and advanced methods with different force and/or moment equilibrium. Furthermore, the minimum factors of safety of different methods for a given slope can be determined. From the practical teaching of the ErosSSA in two courses for Bachelor and Master students, it was found that they were highly satisfied with the accuracy, reliability, and convenience of the ErosSSA according to their feedbacks to a questionnaire. These practical teaching experiences support the ErosSSA to be widely used as a suitable teaching platform in geotechnical engineering.